'Room of Gloom': Reconceptualising Mothers of Children with Disabilities as Experiencing Trauma. Issue 2 (17th February 2020) - Emerson, Anne
Abstract: The experience of having a child with disabilities can be traumatic due to the nature of the child's condition, fears for life, uncertainty about future quality of life and how news of the condition is imparted. Mothers of children with disabilities are known to experience high levels of stress, but participants in this study present evidence of post-traumatic stress. UK services are not designed to support traumatized parents, and health practice may serve to compound distress. The need for effective support for families, including in building social bonds, is highlighted.